POLYPLOIDY AND ITS SIGNIFICANCE IN THE BREEDING OF CAPEOUS PLANTS (Scientific journal of the Fergana State University, 2024)
This article presents information about polyploidy and its selection of cultured spiked plants. Artificial polyploidy in plants was implemented for the first time by G. Winkler in the tomato plant. Based on the fact that more than half of the studied plants are polyploid, M.S. Navashin was one of the first to show that polyploid forms can appear in response to factors of adverse conditions, and that plants changed as a result of such polyploidization are more adaptable to adverse conditions and have a stronger ability to spread. showed.